EPIDEMIOLOGICAL STUDY OF PERTUSSIS IMMUNIZATION EFFECTIVENESS IN VARNA REGION (2009-2014) - Gabriela Tsankova; Eliana Ivanova; Tatina Todorova; Rumen Konstantinov; Neli Ermenlieva; Ianka Draganova (Peytchinski Publishing, 2016)
Pertussis is an acute infectious disease, caused by Bordetella pertussis. Although an effective vaccination program exists in many countries, it is a wide-spread and highly contagious infection. In Varna Region, B. pertussis infection affects different age groups, but the incidence rate is highest in infants under 1 year (12 cases in total), following the group of children at 0-9 years of age (9 cases in total). During the period 2009-2014, a significant decrease in the immunization covering was detected, mainly due on irregular vaccine supply and anti-vaccination movement among parents.